Estudio, aplicación y mejora de la guía metodológica para la gestión de partes interesadas en el Proyecto Hidroituango (2015)
"The purpose of the degree work is to prepare a stakeholder management study, based on the knowledge acquired in the Specialization in Development and Integral Project Management and in the application of the methodological guide developed by the group formed by Jhon Marín, Luz Elvira Gutiérrez and Javier Zuluaga At the same time, the degree work seeks to make the methodological guide and its improvement established as a reference in the national culture of projects for the adequate management of interested parties. The interest of the working group is focused on developing knowledge and deepening the application of methodologies, tools and procedures that allow a more effective management of the relationships between the people and organizations in charge of developing projects and the stakeholders involved in its execution. The degree work, consisting of a technical and applied research work in the Hidroituango project, was developed based on a procedure that began with obtaining information on the current context of hydroelectric projects in Colombia, their relationships with stakeholders and their impacts during its development. Once the context of the hydroelectric projects was framed and the Hidroituango project was chosen as the case to be studied, the degree working group developed a methodological design to be applied. The phases of this methodological design begin with a study of the GMGPI, a design of the application exercise to obtain and classify the information of the case study, and the process for improvement of the GMGPI. "- Excerpt from the Text